Arabidopsis alkaline ceramidase ACER functions in defense against insect herbivory. (18th April 2022) - Huang, Li-Qun; Li, Ping-Ping; Yin, Jian; Li, Yong-Kang; Chen, Ding-Kang; Bao, He-Nan; Fan, Rui-Yuan; Liu, Hao-Zhuo; Yao, Nan
Abstract : Herbivore feeding affects Arabidopsis sphingolipid metabolism; alkaline ceramidase is regulated by the jasmonate pathway and its loss enhances plant resistance to Spodoptera exigua and improves response to wounding and exogenous jasmonate. Abstract: Plant sphingolipids are important membrane components and bioactive molecules in development and defense responses. However, the function of sphingolipids in plant defense, especially against herbivores, is not fully understood. Here, we report that Spodoptera exigua feeding affects sphingolipid metabolism in Arabidopsis, resulting in increased levels of sphingoid long-chain bases, ceramides, and hydroxyceramides. Insect-induced ceramide and hydroxyceramide accumulation is dependent on the jasmonate signaling pathway. Loss of the Arabidopsis alkaline ceramidase ACER increases ceramides and decreases long-chain base levels in plants; in this work, we found that loss of ACER enhances plant resistance to S. exigua and improves response to mechanical wounding. Moreover, acer-1 mutants exhibited more severe root-growth inhibition and higher anthocyanin accumulation than wild-type plants in response to methyl jasmonate treatment, indicating that loss of ACER increases sensitivity to jasmonate and that ACER functions in jasmonate-mediated root growth and secondary metabolism. Transcript levels of ACER were also negatively regulated by jasmonates, and this process involves the transcription factor MYC2. Thus, our findings reveal that ACER is involved in mediating jasmonate-related plant growth and defense and that jasmonates function in regulating the expression of ACER .